Evidence for absence in northern Europe of especially virulent clonal types of Actinobacillus actinomycetemcomitans. - Haubek, D (1995)
Genetic analysis of an Actinobacillus actinomycetemcomitans population consisting of 88 clinically well characterized Finnish isolates performed by multilocus enzyme electrophoresis confirmed that the five serotypes divide into two phylogenetic lineages, one comprising serotypes b and c and one comprising serotypes a, d, and e. There was no association between any subpopulation and the periodontal health status of the subject from whom the isolates originated, suggesting that the role of A. actinomycetemcomitans in periodontitis is largely opportunistic in the population examined. Southern blot analyses of genomic DNA digested with each of the restriction endonucleases MspI, RsaI, and TaqI revealed extremely limited genetic polymorphism of the structural leukotoxin gene, ltxA, and its associated promoter. All isolates hybridized to a 530-bp DNA fragment derived from the promoter region of the leukotoxin gene operon of a minimally leukotoxic A. actinomycetemcomitans strain. Deletion of the 530-bp sequence has been associated with significantly increased toxin production detected among isolates from patients with juvenile periodontitis in North America but was detected neither among the 88 isolates in the present collection analyzed nor among more than 60 strains in another population of northern European A. actinomycetemcomitans isolates analyzed previously.